2018
DOI: 10.1111/aogs.13420
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid does not prevent first‐trimester unexplained recurrent pregnancy loss: A randomized controlled trial

Abstract: Treatment with acetylsalicylic acid did not prevent recurrent miscarriage in women with at least three consecutive miscarriages in the first trimester, of unknown reasons and in the same relationship. The fertility prognosis is very good, the live birth rate being > 80% with or without acetylsalicylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Six out of the eight trials reported the effect of aspirin commenced at <11 weeks' gestation on the rates of preeclampsia. (38,40,50,56,84,85) Four out of the eight trials reported the effect of aspirin started at <11 weeks' gestation on the rates of gestational hypertension. (40,50,84,85) For any hypertensive disorder of pregnancy, there were eight trials reporting the effect of aspirin initiated at <11 weeks' gestation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six out of the eight trials reported the effect of aspirin commenced at <11 weeks' gestation on the rates of preeclampsia. (38,40,50,56,84,85) Four out of the eight trials reported the effect of aspirin started at <11 weeks' gestation on the rates of gestational hypertension. (40,50,84,85) For any hypertensive disorder of pregnancy, there were eight trials reporting the effect of aspirin initiated at <11 weeks' gestation.…”
Section: Resultsmentioning
confidence: 99%
“…(38,40,50,56,84,85) Four out of the eight trials reported the effect of aspirin started at <11 weeks' gestation on the rates of gestational hypertension. (40,50,84,85) For any hypertensive disorder of pregnancy, there were eight trials reporting the effect of aspirin initiated at <11 weeks' gestation. (38,40,50,56,76,(84)(85)(86) Lastly, six and five of the eight trials reported the effect of aspirin commenced at <11 weeks' gestation on the preterm delivery (40,56,76,(84)(85)(86) and fetal growth restriction, (38,40,50,56,86) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations